Clinical and electrocardiographic evaluation during experimental toad poisoning in dogs - Camplesi, A. C. [UNESP]; Sakate, M.; Simao, N. M. B.; Marucio, R.; Mota, F. C. D.; Moya-Araujo, C. F. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
Accidents involving toad poisoning are frequent and dogs are the most common victims; they become poisoned by biting or ingesting a toad. When released in the organism, the venom is absorbed by both the oral mucosa and the digestive tract, initiating its toxic action. The aim of this work was to evaluate the clinical and electrocardiographic aspects of dogs subjected to experimental toad poisoning, as well as their response to treatment with propranolol. Twenty dogs were divided into two groups, a control group (n = 5) and a poisoned group (n = 15). After general anesthesia, the control group received a placebo, while the poisoned group received a venom aliquot through an orogastric tube. Results were tested through multivariate analysis (p < 0.05). The animals in the poisoned group had gastrointestinal symptoms including emesis, intense salivation, hyperemic or congested oral mucosa and pasty diarrhea. Non-responsive mydriasis, nystagmus, depression, stupor, tachypnea, opisthotonus and ataxia were also manifested by 100% of the poisoned animals. Affected dogs had an increase in blood pressure, statistically significant throughout study. Five poisoned animals developed ventricular tachycardia and were treated with propranolol (0.5 mg/kg IV). All propranolol-treated animals returned to normal sinus rhythm, which evidences the efficacy of this drug to treat ventricular arrhythmias caused by toad venom.
Keywords: dogs; toad venom; poisoning; bufotoxin; arrhythmias